Investigating Teachers’ Perception of Using Creative Writing for Promoting Iraqi EFL Preparatory School Students’ Performance in Writing Skill - et. al., Niaam Ali Hasan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aimed to investigate teachers' perception of using creative writing to enhance the performance of Iraqi EFL preparatory school students writing skills .the study community consists of English language teachers in Baghdad governorate. (240) teachers were chosen as a random sample that was randomly selected In Baghdad governorate - Rusafa first to conduct the research. the researcher used the descriptive approach and the questionnaire to collect information, This questionnaire was distributed in paper and electronic form, where the paper questionnaire was identified at (20 )random schools, and the rest of the sample was through the electronic questionnaire. then used the program Spss to statistically analyze the data. The most important findings of the study: Benefiting from creative writing by developing the writing skill of students, Finding educational aids and methods New to be used in teaching, and one of the most important recommendations is to devise new methods and methods in teaching creative writing to students, find a specific time to teach creative writing to students, use new means and technology in the teaching process.